PATHOPHYSIOLOGY OF BRONCHIAL ASTHMA - Razhabova Zebiniso Safarovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract:Bronchial asthma is a chronic inflammatory disease of the airways characterized by bronchoconstriction, airway hyperresponsiveness, and excessive mucus production. It results in episodic airflow obstruction and respiratory distress. This article explores the pathophysiological mechanisms underlying bronchial asthma, highlighting the role of immune responses, inflammation, and airway remodeling in disease progression.